Improving Maine’s Future through Education: Overcoming Challenges and Learning to “Row” Together - Silka, Linda; Hutchins, Karen; Jones, Meredith; Rector, Chris (Maine Policy Review, 2012)
Although people agree that education is a crucial ingredient in the mix of factors that will improve Maine’s economic prospects, we often come at the problem from different angles and develop different methods to improve educational outcomes. In this article, Linda Silka, Karen Hutchins, Meredith Jones, and Chris Rector assert that progress in securing a bright future for Maine requires working together across disciplines and areas of expertise to support education. The authors present nine recommendations for strengthening Maine’s educational systems.
Keywords: Maine; education; collaboration; educational outcomes